Thrombocytopaenia and intraventricular haemorrhage in very premature infants: a tale of two cities. Issue 5 (29th August 2012) - von Lindern, Jeannette S; Hulzebos, Christian V; Bos, Arend F; Brand, Anneke; Walther, Frans J; Lopriore, Enrico
Abstract : Objective: To study whether the incidence of intraventricular haemorrhage (IVH) in very premature infants (<32 weeks gestation) with thrombocytopaenia is lower when using a liberal platelet-transfusion guideline compared with a restrictive guideline. Study design: A retrospective cohort study comparing the incidence of IVH in very premature infants with thrombocytopaenia (platelet count <150×10 9 /l) admitted between 2007 and 2008 to two neonatal intensive care unit in The Netherlands. The restrictive platelet-transfusion unit (N=353 infants <32 weeks gestation) transfused only in case of active haemorrhage and a platelet count <50×10 9 /l. The liberal-transfusion unit (N=326 infants <32 weeks gestation) transfused according to predefined platelet count thresholds. Primary outcome was the incidence and severity of IVH in infants with thrombocytopaenia in both units. Results: The number of infants with thrombocytopaenia that received a platelet transfusion was significantly lower in the restrictive-transfusion unit compared with the liberal-transfusion unit, 15% (21/145) versus 31% (41/141), (p<0.001). The incidence of IVH in infants with thrombocytopaenia in the restrictive-transfusion and liberal-transfusion units was 30% (44/145) and 29% (41/141), respectively (p=0.81). The incidence of severe IVH (grade 3 or 4) in the restrictive-transfusion and liberal-transfusion units was 8% (12/145) and 11% (16/141), respectively (p=0.38). Conclusion: In the restrictive-transfusion unit, the rate of platelet transfusions was significantly lower, but the incidence and severity of IVH was similar to the liberal-transfusion unit.